Social control and the gang: lessons from the legalization of street gangs in Ecuador - Brotherton, David (Critical criminology, 2021)
In 2008, the Ecuadorian Government launched a policy to increase public safety as part of its "Citizens’ Revolution" (La Revolución Ciudadana). An innovative aspect of this policy was the legalization of the country’s largest street gangs. During the years 2016-2017, we conducted ethnographic research with these groups focusing on the impact of legalization as a form of social inclusion. We were guided by two research questions: (1) What changed between these groups and society? and (2) What changed within these groups? We completed field observations and sixty qualitative interviews with group members, as well as multiple formal and informal interviews with government advisors, police leaders and state actors related to the initiative. Our data show that the commitment to social citizenship had a major impact on gang-related violence and was a factor in reducing the nation’s homicide rate. The study provides an example of social control where the state is committed to polices of social inclusion while rejecting the dominant model of gang repression and social exclusion practiced throughout the Americas.